Fingerprint localization based on hybrid TOA, AOA, and RSS measurements - Shuiwei Liu; Lei Tang; Zhangsheng Wang (Discover Applied Sciences)
Abstract This paper presents a novel joint TOA-AOA-RSS fingerprint localization method aimed at reducing the necessity for collecting extensive fingerprint data for database construction. Initially, The Time-of-Arrival(TOA) is employed for coarse localization to narrow down the fingerprint database. Subsequently, Angle-of-Arrivals(AOAs) and Received Signal Strengths(RSSs) were used as feature parameters to construct the fingerprint database together with the coarse localization coordinates obtained from the TOA. Finally, a matching algorithm is utilized to determine the coordinate of the localization point. Additionally, we introduce an improved self adaptive weighted K nearest neighbor (ISAWKNN) algorithm is proposed based on Hybrid TOA,AOA, and RSS measurements. Simulation results illustrate the proposed algorithm improving the localization accuracy.